Self-reported Sleep Problems Related to Amyloid Deposition in Cortical Regions with High HOMER1 Gene Expression. (11th November 2019) - Fjell, Anders M; Sederevicius, Donatas; Sneve, Markus H; de Lange, Ann-Marie Glasø; Bråthen, Anne CecilieSjøli; Idland, Ane-Victoria; Watne, Leiv Otto; Wang, Yunpeng; Reinbold, Céline; Dobricic, Valerija; Kilpert, Fabian; Blennow, Kaj; et al.
Abstract: Sleep problems are related to the elevated levels of the Alzheimer's disease (AD) biomarker β-amyloid (Aβ). Hypotheses about the causes of this relationship can be generated from molecular markers of sleep problems identified in rodents. A major marker of sleep deprivation is Homer1a, a neural protein coded by the HOMER1 gene, which has also been implicated in brain Aβ accumulation. Here, we tested whether the relationship between cortical Aβ accumulation and self-reported sleep quality, as well as changes in sleep quality over 3 years, was stronger in cortical regions with high HOMER1 mRNA expression levels. In a sample of 154 cognitively healthy older adults, Aβ correlated with poorer sleep quality cross-sectionally and longitudinally ( n  = 62), but more strongly in the younger than in older individuals. Effects were mainly found in regions with high expression of HOMER1 . The anatomical distribution of the sleep-Aβ relationship followed closely the Aβ accumulation pattern in 69 patients with mild cognitive impairment or AD. Thus, the results indicate that the relationship between sleep problems and Aβ accumulation may involve Homer1 activity in the cortical regions, where harbor Aβ deposits in AD. The findings may advance our understanding of the relationship between sleep problems and AD risk.